Elaboração e análise do índice de desenvolvimento sustentável das cidades (IDSC) na Região de Integração do Baixo Amazonas (RIBA) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study aims to assess the level of sustainable development of the thirteen cities that make up the Lower Amazon Integration Region (RIBA), in the state of Pará, using the Sustainable Development Index of Cities (IDSC), a way to measure and promote sustainability based on the Sustainable Development Goals (SDGs) of the UN 2030 Agenda. This leads to the following research problem: "Does the Sustainable Development Index of Cities in the Lower Amazon Integration Region (IDSC-RIBA) contribute to the comparative analysis of the Sustainable Development Goals (SDGs)?" To answer this question, we used methodologies combined with theoretical research, including bibliographic and documentary reviews, as well as quantitative research based on secondary data from the IDSC-BR, including the application of statistical formulas to consolidate the results. Thus, we analyzed the performance of individual cities and each of the 17 SDGs, calculating the regional average to identify the main SDG advances. The results indicate that RIBA has a very low level of sustainable development, with an overall average of 36.9. Another alarming factor is that few cities achieved satisfactory (very high) levels of development in the SDGs, only Curuá and Faro, highlighting the fact that they alone cannot increase RIBA's SDG average. The conclusion points out that RIBA faces many structural challenges and socioeconomic inequalities, issues that are related to the SDGs and also reinforce the need for more public policies.
Keywords: Desenvolvimento sustentável; IDSC; sustentabilidade; políticas públicas; RIBA; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS